The Experiences of Tiresias : The Feminine and the Greek Man - Loraux, Nicole (Book collections on Project MUSE., 1995)
Nicole Loraux has devoted much of her writing to charting the paths of the Greek "imaginary," revealing a collective masculine psyche fraught with ambivalence as it tries to grasp the differences between nature and culture, body and soul, woman and man. The Experiences of Tiresias, its title referring to the shepherd struck blind after glimpsing Athena's naked body, captures this ambivalence in exploring how the Greek male defines himself in relationship to the feminine. In these essays, Loraux disturbs the idea of virile men and feminine women, a distinction found in official discourse and aimed at protecting the ideals of male identity from any taint of the feminine. Turning to epic and to Socrates, however, she insists on a logic of an inclusiveness between the genders, which casts a shadow over their clear, officially defined borders. The emphasis falls on the body, often associated with feminine vulnerability and weakness, and often dissociated from the ideal of the brave, self-sacrificing male warrior. But heroes such as the Homeric Achilles, who fears yet fights bravely, and Socrates, who speaks of the soul through the language of the body, challenge these representations. The anatomy of pain, the heroics of childbirth, the sorrows of tears, the warrior's wounds, and the madness of the soul: all these experiences are shown to engage with both the masculine and the feminine in ways that do not denigrate the experiences for either gender. Originally published in 1995. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905